Method for the preparation of nanoporous zinc and its use in zinc batteries

CN116162974BActive Publication Date: 2026-11-03THE HONG KONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111506478.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-24
Filing Date
2021-12-10
Publication Date
2026-11-03
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

Existing methods for preparing porous zinc are complex and difficult to adjust porosity and zinc fiber size, resulting in poor rechargeability of zinc batteries.

Method used

By applying a reduction potential of -1.4 V to -1.6 V relative to the Ag/AgCl reference electrode to the zinc powder compact in an electrochemical cell, combined with the use of a rigid organic material separator and an appropriate electrolyte concentration, the densification process of the zinc compound on the conductive substrate is regulated to form an integrated nanoporous zinc.

Benefits of technology

A simple and easy-to-operate method for preparing nanoporous zinc with uniform pores and zinc fibers has been achieved, which improves the rechargeability and cycle life of zinc batteries and is suitable for secondary alkaline batteries such as nickel-zinc, silver-zinc and zinc-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116162974B_ABST
    Figure CN116162974B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical cells, and specifically relates to a method for preparing integrated nanoporous zinc in an electrochemical cell, as well as the integrated nanoporous zinc prepared by the method, the electrode prepared from the integrated nanoporous zinc, and the cell. The method is simple and scalable, and the nanoporous zinc obtained thereby has a bicontinuous pore and zinc fiber, and the size of each of the pore and the zinc fiber is uniform. The cell comprising the electrode prepared from the nanoporous zinc has a longer rechargeability or cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical batteries, specifically relating to the preparation of a self-supporting porous zinc electrode from a powder compact made of zinc compounds using an electrochemical method. Background Technology

[0002] Zinc metal has attracted considerable attention due to its underutilized potential in rechargeable batteries. As one of the most abundant metals on Earth, zinc has a theoretical capacity of 3694 Ah / L. The slow hydrogen evolution reaction on zinc's surface allows it to operate in aqueous solutions, particularly alkaline electrolytes, eliminating any fire hazard and reducing costs. It can serve as a substitute for expensive metal hydrides to fully utilize the mature alkaline nickel batteries. It can also be paired with an air cathode to provide practical energy densities up to 400 Wh / kg. However, under real-world conditions, neither type of battery achieves sufficiently long cycle life—neither possesses high areal capacity, high depth of discharge, or low-capacity electrolytes. Most fail within 150 cycles, making them uncompetitive compared to the continuously improving lithium-ion batteries.

[0003] The root cause of the failure lies in the suboptimal phase transition pathway between zinc and zinc oxide during the battery reaction. In alkaline electrolytes, the most common zinc anode begins with a bed of predominantly ZnO powder, which is partially reduced to zinc metal during the first charging step. This reduction can stimulate long-range transport of zincate ions in the electrolyte, forming numerous zinc particles that grow cyclically, at the cost of sacrificing properties such as electrode uniformity and conductivity. The dense particles, acting as reaction hotspots, are covered by a thin layer of zinc oxide, which passivates them and prevents complete discharge. Meanwhile, zinc in the rest of the electrode is attracted to these hotspots, leaving depletion areas that are even visible to the naked eye—a shape change phenomenon that has plagued the rechargeability of zinc anodes for decades. A solution to this problem must simultaneously achieve two goals: a uniform distribution of zinc formation and a sustainable transition between zinc and zinc oxide.

[0004] US Patent Application US20170338479A1 discloses an electrochemical battery comprising: an anode current collector; an anode in electrical contact with the anode current collector; an electrolyte; a cathode current collector; a cathode containing silver or silver oxide in electrical contact with the anode current collector; and a separator between the anode and the cathode. The anode is made by: providing a mixture comprising zinc powder and a liquid emulsion; drying the mixture to form a sponge; annealing and / or sintering the sponge in an inert atmosphere or under vacuum at a temperature below the melting point of zinc to form an annealed and / or sintered sponge having a zinc surface; and heating and annealing and / or sintering the sponge in an oxidizing atmosphere at a temperature above the melting point of zinc to form an oxide sponge comprising a zinc oxide shell on the surface of the oxide sponge. The anode comprises: a continuous network containing zinc; a continuous network of voids penetrating the zinc network; and zinc bridges connecting the zinc particle cores. The electrolyte fills the voids.

[0005] US Patent Application US20170025677A1 discloses a supercrystalline dendritic nanoporous zinc foam suitable for use as an electrode, preferably an anode. Zinc foam is a three-dimensional dendritic network, including nanoscale structures, possessing electrochemical activity and conductivity. Therefore, in some preferred embodiments, the zinc foam electrode is a nanoporous zinc structure comprising primary and secondary dendrites. The supercrystalline dendritic nanoporous zinc foam exhibits at least twice the specific surface area of ​​a zinc block. This high relative surface-to-volume ratio provides better and more uniform charge distribution, better capacity retention over multiple charge-discharge cycles, and a longer effective battery life.

[0006] Patent application WO2019183083A1 provides a composition comprising a nanoporous material containing interconnecting fibers defining pores therebetween, the pores being open to an environment outside the nanoporous material. The nanoporous material optionally contains a metal having a standard reduction potential less than that of a standard hydrogen electrode (SHE) at 0V vs SHE, and the pores are characterized as having an average cross-section ranging from about 3 to 100 nm. The invention also provides a power battery comprising: a composition according to the invention, optionally placed in a removable cartridge; a quantity of water, the power battery configured to influence contact between the composition and the water; and a collector configured to collect hydrogen evolved from the contact between the water and the composition.

[0007] As can be seen from the above, existing technologies for preparing porous zinc mainly include two methods: one using electroplating, and the other involving sintering and calcination steps. Both methods have many drawbacks. For example, these methods are relatively complex to operate, the scale is not adjustable, and it is difficult or impossible to adjust the porosity, tortuosity, and pore characteristics of the produced porous zinc. Furthermore, these methods cannot produce porous zinc with a uniform nanoscale structure. Therefore, when porous zinc obtained by these two methods is used to prepare battery electrodes, the resulting batteries have poor rechargeability (i.e., cycle life under deep discharge).

[0008] Therefore, there is an urgent need in the field to find a method to prepare nanoporous zinc with zinc fibers and pores of the desired and consistent size in order to further improve the rechargeability of zinc batteries. Summary of the Invention

[0009] Given the shortcomings of the existing technology mentioned above, further exploration is still needed in terms of raw materials for zinc electrode manufacturing and the preparation methods of these raw materials, in order to improve the rechargeability of zinc batteries made from these electrodes and truly leverage the advantages of zinc as an electrode.

[0010] Therefore, in a first aspect, the present invention provides a method for preparing integrated nanoporous zinc in an electrochemical cell, the electrochemical cell comprising a working electrode, a separator, an electrolyte, a reference electrode, and a counter electrode, the working electrode comprising a conductive substrate and a zinc powder compact, wherein the zinc powder compact is obtained by densifying zinc compound powder on the conductive substrate, the method comprising applying a reduction potential of -1.4 V to -1.6 V relative to an Ag / AgCl reference electrode to the working electrode to reduce the zinc compound, thereby forming integrated nanoporous zinc on the conductive substrate.

[0011] In a second aspect, the present invention provides an integrated nanoporous zinc having dual continuous pores and zinc fibers, wherein each of the pores and zinc fibers has a uniform size of 200 nm to 1000 nm.

[0012] In a third aspect, the present invention provides an electrode comprising an integrated nanoporous zinc and a conductive substrate to which the second aspect of the present invention is attached.

[0013] In a fourth aspect, the present invention provides a battery comprising an anode having an electrode of the third aspect of the present invention as the anode.

[0014] This invention has one or more of the following technical effects:

[0015] (1) Compared with the existing methods for preparing porous zinc by electroplating or by sintering and calcination, the present invention provides a new and scalable method for preparing nanoporous zinc. This method is simple and easy to operate. The zinc powder briquettes can be prepared into nanoporous zinc simply by applying a suitable reduction potential to the zinc powder briquettes.

[0016] (2) The method of the present invention can prepare integrated nanoporous zinc with high loading and high areal capacity by customizing the loading amount of zinc precursor;

[0017] (3) The method of the present invention is implemented in an electrochemical cell. By adjusting multiple parameters of the electrochemical cell, such as the distance between the separator and the working electrode, the type of zinc compound, the reduction overpotential, the electrolyte formulation, or a combination thereof, the method of the present invention can adjust the material parameters such as porosity, tortuosity, and pore characteristics of the obtained nanoporous zinc. Attached Figure Description

[0018] The accompanying drawings, together with the embodiments of the present invention, provide a further explanation of the invention and constitute a part of the specification. It is obvious that the drawings described below only illustrate some embodiments of the invention and do not constitute a limitation thereof. Those skilled in the art will be able to obtain other embodiments based on these drawings without any inventive effort.

[0019] Figure 1 A schematic diagram of the structure of an electrochemical cell for implementing the method of the present invention is shown. The cell includes an anode (working electrode) 1, a separator 2 on the anode, a reference electrode 3, and a cathode (counter electrode) 4.

[0020] Figure 2 A scanning electron microscope (SEM) image of nanoporous zinc prepared from zinc oxide as a precursor is shown, which reveals that the nanoporous zinc has a distinct bicontinuous structure of pores and fibers.

[0021] Figure 3 The image shows a SEM image of nanoporous zinc prepared from zinc carbonate as a precursor. The image shows that the nanoporous zinc has distinctly spherical particles with a bicontinuous structure.

[0022] Figure 4 The polarization curves of porous zinc are shown;

[0023] Figure 5 It showed 25mA / cm 2 The stability performance of porous zinc under charge and discharge conditions at 40% DOD cycling;

[0024] Figure 6 It showed 25mA / cm 2The stability performance of porous zinc under charge and discharge conditions at 60% DOD cycling. Detailed Implementation

[0025] The present invention will now be clearly and completely described in conjunction with specific embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments that can be obtained by those skilled in the art based on the embodiments given in this application are within the protection scope of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the subject matter pertains. Before a detailed description of the invention, the following definitions are provided to better understand it.

[0027] When a numerical range is provided, such as a concentration range, percentage range, or ratio range, it should be understood that, unless the context explicitly specifies otherwise, all intermediate values ​​between the upper and lower limits of the range, up to one-tenth of the lower limit unit, and any other values ​​or intermediate values ​​within the range are included in the subject matter. The upper and lower limits of these smaller ranges may be independently included in the smaller range, and such embodiments are also included in the subject matter, limited by any specific excluded limit values ​​within the range. Where the range includes one or two limit values, the range excluding any one or both of those included limit values ​​is also included in the subject matter.

[0028] Throughout the application, many implementations use expressions such as "comprising," "including," or "basically / mainly composed of...". These expressions are generally understood as open-ended, indicating that they include not only the elements, components, parts, or method steps specifically listed after the statement, but also other elements, components, parts, or method steps. However, in this document, the expressions "comprising," "including," or "basically / mainly composed of..." can also be understood as closed-ended in certain situations, indicating that they only include the elements, components, parts, or method steps specifically listed after the statement, excluding any other elements, components, parts, or method steps. In this case, the expression is equivalent to the expression "composed of...".

[0029] To better understand this teaching and without limiting its scope, all figures and other numerical values ​​used in the specification and claims to express quantities, percentages, or proportions should, in all cases, be understood to be modified by the term "about". Therefore, unless otherwise stated, the numerical parameters set forth in the following specification and appended claims are approximate values ​​that may vary depending on the desired properties sought. Each numerical parameter should be interpreted at least based on the reported significant figures and by applying common rounding techniques.

[0030] As mentioned above, there is an urgent need in the art to find a method to prepare nanoporous zinc with zinc fibers and pores of the desired and consistent size in order to further improve the rechargeability of zinc batteries.

[0031] Therefore, in a first aspect, the present invention provides a method for preparing integrated nanoporous zinc in an electrochemical cell, the electrochemical cell comprising a working electrode, a separator, an electrolyte, a reference electrode, and a counter electrode, the working electrode comprising a conductive substrate and a zinc powder compact, wherein the zinc powder compact is obtained by densifying zinc compound powder on the conductive substrate, the method comprising applying a reduction potential of -1.4 V to -1.6 V relative to an Ag / AgCl reference electrode to the working electrode to reduce the zinc compound, thereby forming integrated nanoporous zinc on the conductive substrate.

[0032] As described above, the method of the present invention is carried out in an electrochemical cell, which includes a working electrode as the anode, a separator, an electrolyte, a reference electrode, and a counter electrode as the cathode. Conventional electrochemical cells typically use a flexible separator to separate the anode and cathode; however, in the electrochemical cell implemented by the method of the present invention, a separator is used instead of a separator, thereby enabling adjustment of the thickness and porosity of the nanoporous zinc to be formed.

[0033] Similar to the separator, the separator is also located between the working electrode and the counter electrode, and has the same function as the separator, namely, separating the positive and negative electrode plates to prevent direct contact and short circuit, and also has the functions of ion conduction and insulation. However, the separator and the separator also have the following differences in structure and function:

[0034] First, the partition is made of a rigid organic material. In this invention, "rigid" refers to the property of a material that is not easily deformed under external force. There are many types of rigid organic materials that can be used for the partition, such as acrylic materials, polypropylene (PP), polyethylene (PE), and / or polyetherketone (PEEK), but are not limited to these.

[0035] Therefore, in one embodiment, the separator is located between the working electrode and the counter electrode, and the separator is made of a rigid organic material. In a preferred embodiment, the rigid organic material includes acrylic materials, polypropylene (PP), polyethylene (PE), and / or polyetherketone (PEEK).

[0036] Secondly, the inventors discovered that the distance between the separator and the working electrode affects the porosity and zinc fiber size of the final formed nanoporous zinc. Therefore, by adjusting the distance between the separator and the working electrode, the thickness, porosity, and zinc fiber size of the final porous zinc electrode can be adjusted, as shown in equation (1):

[0037]

[0038] Where ε is the porosity of the porous zinc electrode, ε0 is the initial porosity of the zinc precursor (i.e., zinc compound), α is the ratio of the distance between the separator and the working electrode to the initial thickness of the working electrode, and V m,锌化合物 With V m,Zn These are the molar volumes of the zinc compound and zinc, respectively.

[0039] The distance between the separator and the working electrode is positively correlated with the porosity and zinc fiber size of the formed nanoporous zinc. Specifically, the smaller the distance between the separator and the working electrode, for example, when α = 1 (at which point the separator is in complete contact with the working electrode), the smaller the porosity of the resulting nanoporous zinc and the larger the zinc fiber size, i.e., the coarser the zinc fiber; conversely, the larger the distance between the separator and the working electrode, for example, when α = 2, the larger the porosity of the resulting nanoporous zinc and the smaller the zinc fiber size, i.e., the finer the zinc fiber. Therefore, the distance between the separator and the working electrode can be correlated with the porosity and / or zinc fiber size of the nanoporous zinc to be formed in advance, and the distance between the separator and the working electrode can be adjusted according to the required porosity and / or zinc fiber size to obtain the desired nanoporous zinc.

[0040] Therefore, in one embodiment, the method further includes adjusting the porosity and zinc fiber size of the formed nanoporous zinc by adjusting the distance between the separator and the working electrode. Preferably, the porosity of the formed nanoporous zinc is increased and / or the zinc fiber size is reduced by increasing the distance between the separator and the working electrode, or the porosity of the formed nanoporous zinc is reduced and / or the zinc fiber size is increased by decreasing the distance between the separator and the working electrode.

[0041] Besides the distance between the separator and the working electrode affecting the internal structure of the nanoporous zinc, the concentration of hydroxide ions in the electrolyte and the type of electrolyte in the electrochemical cell also affect the final internal structure of the nanoporous zinc.

[0042] The inventors have discovered that the hydroxide ion concentration in the alkaline solution significantly affects the internal structure of the final formed nanoporous zinc. Nanoporous zinc with the desired microstructure can be obtained when the hydroxide ion concentration is between 3M and 6M. When the hydroxide ion concentration is below 3M, the reduction rate is too slow and the reaction time is too long; conversely, when the hydroxide ion concentration is above 6M, the zinc oxide dissolves too quickly, which is detrimental to the formation of nanoporous zinc. Therefore, in one embodiment, the electrolyte is an alkaline solution with a hydroxide ion concentration of 3M to 6M.

[0043] The inventors have also discovered that the desired nanoporous zinc can be obtained by using alkali metal hydroxides such as sodium hydroxide (NaOH), potassium hydroxide (KOH), lithium hydroxide (LiOH), etc. Therefore, in one embodiment, the alkali is an alkali metal hydroxide. The alkali metal hydroxide can be sodium hydroxide, potassium hydroxide, lithium hydroxide, etc.

[0044] In addition, other metal ions that can participate in the reduction reaction, such as bismuth, indium, and calcium ions, can be added to the electrolyte. These metal ions are reduced and doped into the final nanoporous zinc structure during the reduction of the zinc compound, which helps to reduce side reactions such as hydrogen evolution during battery operation.

[0045] In this invention, the working electrode serving as the anode includes a conductive substrate and a zinc powder compact, wherein the zinc powder compact is obtained by densifying zinc compound powder on the conductive substrate.

[0046] First, the conductive substrate serves a supporting function and, due to its conductive properties, is in most cases made of metal. Furthermore, there are no particular requirements regarding the form of the conductive substrate, as long as it provides sufficient support. Therefore, in one specific embodiment, the conductive substrate is a metal substrate such as metal foam, metal foil, or metal mesh. In another specific embodiment, the metal can be copper, titanium, tin, etc.

[0047] Furthermore, the metal substrate can be tin-plated before densifying the zinc compound powder onto the conductive substrate. Tin plating is used to reduce hydrogen evolution side reactions on the copper surface. Therefore, in an optional embodiment, the metal substrate is tin-plated.

[0048] Secondly, as mentioned above, zinc powder briquettes are obtained by densifying zinc compound powder on the conductive substrate.

[0049] Zinc compounds refer to any compound containing zinc that can be reduced to elemental zinc, such as zinc oxide, zinc carbonate, zinc chloride, and / or zinc acetate. The inventors have discovered that by using different zinc compounds as reactants, nanoporous zinc with not entirely identical microstructures can be obtained. Therefore, in practice, a suitable zinc compound can be selected as a reactant based on the desired microstructure of the nanoporous zinc.

[0050] Furthermore, the densification can be achieved in any suitable manner, but is typically achieved mechanically, for example by applying a certain force to zinc compound powder laid on a conductive substrate, thereby preparing the discrete powder form of zinc compound into a bulk or integrated form. The resulting conductive substrate and bulk zinc compound (i.e., zinc powder briquettes) can be used as the working electrode in the electrochemical battery of the present invention. It is understood that the pressure applied to the zinc powder briquettes will affect the density of the zinc powder briquettes, and thus affect the final microstructure of the nanoporous zinc. Specifically, according to formula (1), if the pressure is too high, for example, exceeding 9 tons, the smaller ε0 is, and the smaller the porosity of the obtained nanoporous zinc; if the pressure is too low, for example, below 0.5 tons, the zinc compound powder may not be able to completely bond, resulting in powder shedding and splitting. Therefore, in one embodiment, the zinc powder briquettes are obtained by densifying the zinc compound powder on the conductive substrate by applying a pressure of 0.5-9 tons.

[0051] Electrode capacity can also be adjusted by customizing the loading amount of zinc compound powder on the conductive substrate. This can be chosen based on specific application requirements.

[0052] During the preparation of the zinc powder briquettes, other additives can be incorporated into the zinc compound powder to impart additional properties or functions. For example, carbon black, carbon fibers, antimony oxide, and / or calcium hydroxide can be incorporated, thereby making the reduction reaction more uniform.

[0053] A reference electrode is also used in the electrochemical cell; the reference electrode serves as a reference when measuring various electrode potentials. In one embodiment, the reference electrode may be an Ag / AgCl electrode, a mercury / mercury oxide electrode, or a standard hydrogen electrode. In a preferred embodiment, the reference electrode may be an Ag / AgCl electrode.

[0054] In the method of this invention, by applying a certain reduction potential to the working electrode, the zinc compound in the zinc powder compact constituting part of the working electrode can be reduced to elemental zinc, thereby forming an integrated nanoporous zinc on the conductive substrate. The magnitude of the reduction potential has a significant impact on the microstructure of the final nanoporous zinc: if the reduction potential is lower than -1.6 V vs Ag / AgCl reference electrode, the hydrogen evolution side reaction during the reduction process is more severe, and the resulting nanoporous zinc will have uneven macropores; if the reduction potential is higher than -1.4 V vs Ag / AgCl reference electrode, the zinc compound cannot be fully reduced, resulting in the inability to obtain nanoporous zinc. Therefore, in one embodiment, the reduction potential is any reduction potential between -1.4 V and -1.6 V (vs Ag / AgCl electrode), for example -1.4 V, -1.45 V, -1.5 V, -1.55 V, and -1.6 V (vs Ag / AgCl electrode). Furthermore, the specific reduction potential values ​​given in this article are relative to the Ag / AgCl reference electrode. When using other reference electrodes that are not Ag / AgCl reference electrodes, the specific reduction potential values ​​given in this article relative to the Ag / AgCl reference electrode can be converted to obtain the specific reduction potential values ​​relative to the other reference electrode, which is within the capabilities of those skilled in the art.

[0055] Furthermore, sufficient time is required to apply the reduction potential, as insufficient application time will result in an incomplete reduction reaction. The application time of the reduction potential is generally determined when the reduction current no longer changes or based on the theoretical capacity of the zinc precursor.

[0056] In summary, the method for preparing nanoporous zinc of the present invention can change the zinc fiber size and / or pore size of the prepared integrated nanoporous zinc by adjusting the reduction potential, changing the composition or concentration of the electrolyte, adjusting the distance from the separator to the working electrode, or by one or more other means. Therefore, the method of the present invention can easily produce nanoporous zinc with the desired microstructure by adjusting factors such as reaction conditions and parameters, and has extremely high adjustability and specificity.

[0057] Furthermore, the method of the present invention does not require the addition of additional additives to control the morphological uniformity of zinc deposition, nor does it require the addition of polymer binders to maintain the integrity of zinc particles, nor does it require the addition of additives to inhibit dendrite formation, nor does it require additives such as emulsifiers or other metals to help form porous zinc. Compared with existing technology methods, it is simpler and easier to implement.

[0058] Furthermore, the nanoporous zinc prepared by the method of this invention possesses unique combined characteristics not found in existing technologies, namely, uniform pores and zinc fibers with a size range of approximately 200-1000 nm, a pore structure that is almost entirely open pores, a continuous zinc phase, and an integrated structure. These combined characteristics make it highly suitable for applying such nanoporous zinc to batteries, and can achieve better rechargeability.

[0059] In a second aspect of the invention, an integrated nanoporous zinc is provided, the integrated nanoporous zinc having dual continuous pores and zinc fibers, wherein each of the pores and zinc fibers has a uniform size of 200 nm to 1000 nm.

[0060] It is understood that the integrated nanoporous zinc of this aspect of the present invention can be prepared by the method of the first aspect of the present invention.

[0061] In this invention, the term "double continuity" refers to two aspects: firstly, the zinc fibers in the nanoporous zinc are interconnected; secondly, the vast majority (e.g., at least 70%, 75%, 85%, 90%, 95%, 96%, 97%, 98%, 99%, or even 100%) of the pores in the nanoporous zinc are interconnected. That is, these pores are interconnected, and the amount of closed pores contained within them is insufficient to affect the function of the nanoporous zinc as an electrode. Therefore, the vast majority of pores are directly or indirectly connected to the outside environment. In this way, when such nanoporous zinc is used to prepare electrodes and these electrodes are used in batteries, the electrolyte in the battery can permeate the entire nanoporous zinc structure, achieving a more uniform current distribution and reducing uneven concentration gradients and anodic polarization losses.

[0062] Furthermore, the pore and zinc fiber sizes of the integrated nanoporous zinc are uniform and consistent with the permeation dissolution mechanism. In this document, "uniform pore and zinc fiber sizes" means that both the pore and zinc fiber sizes are distributed within a specific numerical range, for example, between 200 nm and 1000 nm. Within this range, the nanoporous zinc effectively maintains its structural stability and ensures a uniform current distribution when used as an electrode.

[0063] As described in the first aspect of this invention, many types of zinc powder precursors can be used as precursors for synthesizing nanoporous zinc, such as zinc oxide, zinc carbonate, zinc chloride, and / or zinc acetate. It is understood that the microstructure of the nanoporous zinc obtained using different zinc powder precursors will vary. For example, when using zinc oxide as a raw material, the obtained nanoporous zinc exhibits a relatively simple primary structure composed of bicontinuous pores and zinc fibers, with each pore and zinc fiber having a uniform size of 200 nm to 1000 nm. As another example, when using zinc carbonate as a raw material, the obtained integrated nanoporous zinc exhibits different hierarchical structural morphologies; specifically, the integrated nanoporous zinc exhibits a primary structure and a secondary structure, wherein the primary structure is in the form of spherical particles, each containing bicontinuous pores and fibers, serving as the secondary structure. Therefore, by selecting different zinc compound precursors as raw materials, the final integrated nanoporous zinc can possess a microstructure specific to that precursor, i.e., pore size and zinc fiber size specific to that precursor compound.

[0064] In one embodiment, the integrated nanoporous zinc is prepared as a working electrode comprising a zinc oxide powder compact, and the integrated nanoporous zinc has only a primary structure consisting of pores and zinc fibers.

[0065] In another embodiment, the integrated nanoporous zinc is prepared using a working electrode comprising a zinc carbonate powder compact. The integrated nanoporous zinc has a primary structure of spherical particles, and these spherical particles contain bicontinuous pores and zinc fibers as a secondary structure. Furthermore, it should be understood that this integrated nanoporous zinc, in addition to having nanoscale pores, also possesses micrometer-scale pores.

[0066] It should be noted that, as described in the first aspect above, the nanoporous zinc is obtained by applying a reduction potential to a zinc powder compact obtained by densifying zinc compound powder on a conductive substrate. Therefore, the resulting integrated nanoporous zinc is self-supporting, possesses a certain mechanical strength, and can be cut arbitrarily while maintaining its structural integrity. Thus, the integrated nanoporous zinc of this invention is easier to promote and apply in industry, and can be readily used to prepare batteries of different sizes and specifications.

[0067] In a third aspect, the present invention provides an electrode comprising an integrated nanoporous zinc and a conductive substrate to which the second aspect is attached.

[0068] As described above, the integrated nanoporous zinc of the present invention has a high relative surface area, which makes the electrode made from the porous zinc have a better and more uniform charge distribution, better charge capacity retention in multiple charge-discharge cycles, and a longer effective life of the rechargeable battery.

[0069] As the anode of a secondary alkaline battery, it has better rate performance, longer cycle stability and structural retention while having a large depth of charge and discharge. It can be directly used as the anode in rechargeable alkaline batteries (such as nickel-zinc, silver-zinc and zinc-air) to achieve good rate performance, long cycle life and structural stability during deep discharge.

[0070] In a fourth aspect, the present invention provides a battery comprising an anode having an electrode of the third aspect of the present invention as the anode.

[0071] Unlike batteries in the prior art, batteries using electrodes made of nanoporous zinc as the anode exhibit excellent rechargeability, or cycle life. As an example, the battery of this invention has a cycle life of 200 cycles at 40% depth of discharge (DOD). As another example, it has a cycle life of 100 cycles at 60% depth of discharge (DOD). The excellent rechargeability of the battery of this invention is due, on the one hand, to the uniform distribution of pores and fibers in the formed nanoporous zinc, and on the other hand, to the sustainable transformation between zinc and zinc oxide, which manifests as high depth of discharge, more cycle counts, high coulombic efficiency, etc.

[0072] In one embodiment, the battery is a secondary battery. In a specific embodiment, the secondary battery is a nickel-zinc battery, a silver-zinc battery, or a zinc-air battery.

[0073] For nickel-zinc batteries, given their high safety, low cost, and moderate energy density, the primary market will be backup power. For zinc-air batteries, in addition to backup power, drones and electric vehicles are also potential applications due to their high energy density and low cost.

[0074] Example

[0075] In the following description, specific details are outlined for purposes of explanation and not limitation in order to provide a thorough understanding of this disclosure.

[0076] Example 1: Preparation of nanoporous zinc based on zinc oxide

[0077] A typical bicontinuous porous zinc oxide (ZnO) was prepared by electrochemical reduction of Zn. First, a tin (Sn) substrate was deposited on a copper foam (1.6 mm thick, MTI) at a constant potential under conditions of -1 V (vs Ag / AgCl, in saturated KCl) in an electrolyte containing 0.1 M SnCl2 and 0.4 M K4P2O7. The final tin-deposited copper foam was rinsed with deionized water and ethanol and dried as the substrate. Then, a certain amount of material with a designed capacity of 50 mAh / cm³ was deposited under 1 ton of hydraulic pressure.2 Commercially available zinc oxide powder (J&K) was directly and uniformly pressed onto tin-plated copper foam. Using a self-made electrochemical cell (with Ni foam as the counter electrode), a bias voltage of 1.55 V to 1.6 V (vs Ag / AgCl, in saturated KCl) was maintained in 3 M KOH until only a weak and flat hydrogen evolution current remained, thus converting zinc oxide to zinc. After reduction, the sample was placed sequentially in acetone and methanol for at least 1 h to remove residual H₂O and KOH, and then vacuum dried at room temperature. The nanoporous zinc thus prepared was cut and used directly as an electrode. The resulting morphology was characterized using scanning electron microscopy (SEM).

[0078] Figure 2 Scanning electron microscopy (SEM) images of nanoporous zinc prepared using zinc oxide as a raw material are shown. As can be seen from the images, the resulting nanoporous zinc exhibits a single-layer structure, in which zinc fibers are interconnected, with pores uniformly distributed among them. Almost all of these pores are open, meaning that even the pores located within the nanoporous zinc structure are connected to the outside environment. Therefore, when an electrode containing this structure is immersed in an electrolyte, the electrolyte can fully fill the nanoporous zinc structure. Furthermore, measurements show that the zinc fibers and pores have a size of 200-1000 nm, indicating that the zinc fibers and pores have uniform size, which has excellent effects on battery performance.

[0079] Example 2: Preparation of nanoporous zinc based on zinc carbonate

[0080] A typical bicontinuous porous zinc substrate was prepared by electrochemically reducing zinc carbonate (ZnCO3) to Zn. First, a tin (Sn) substrate was deposited on copper foam (1.6 mm thick, MTI) at a constant potential under a -1 V (vs Ag / AgCl, in saturated KCl) electrolyte containing 0.1 M SnCl2 and 0.4 M K4P2O7. The final tin-deposited copper foam was rinsed with deionized water and ethanol and dried as the substrate. Then, a certain amount of ZnCO3 powder was directly pressed onto the tin-plated copper foam under 1 ton of hydraulic pressure. A self-made electrochemical cell (using Ni foam as the counter electrode) was then used to maintain a bias voltage of 1.55 V to 1.6 V (vs Ag / AgCl, in saturated KCl) in 3 M KOH until only a weak and flat hydrogen evolution current remained, thereby reducing the zinc carbonate in the powder compact to zinc. The reduced sample was sequentially immersed in acetone and methanol for at least 1 hour to remove H₂O and KOH residues, and then vacuum dried at room temperature. The prepared porous zinc can be cut and used directly as a battery anode. The morphology of the obtained sample was characterized by scanning electron microscopy (SEM), as shown below. Figure 3 As shown.

[0081] Figure 3 Scanning electron microscopy (SEM) images of nanoporous zinc prepared using zinc carbonate as a raw material are shown. The images reveal a multi-layered structural morphology of the nanoporous zinc. Specifically, the nanoporous zinc is composed of spherical particles uniformly distributed throughout the structure, forming the primary structure. Each spherical particle also contains continuous pores and zinc fibers, forming the secondary structure. Similar to nanoporous zinc structures obtained through oxidation, the zinc fibers in this nanoporous zinc are interconnected, and almost all the uniformly distributed pores are open pores. Therefore, when an electrode containing this structure is immersed in an electrolyte, the electrolyte can fully fill the nanoporous zinc structure. Furthermore, measurements show that the zinc fibers and pores in this nanoporous zinc have a size of 200-1000 nm, indicating a uniform size that is highly beneficial for battery performance.

[0082] Example 3: Application of nanoporous zinc as an anode in nickel-zinc batteries

[0083] The electrochemical performance of nanoporous zinc in terms of rate capability (C-rate) and stability was investigated in nickel-zinc batteries. The configuration and assembly of the nickel-zinc battery is a simple coin cell design. Square (0.25 cm²) cells were assembled in 2032 coin cell types. 2 Nanoporous zinc-based anode. From a fully charged commercial NiMH AAA battery (approximately 55 mAh / cm³). 2 2600mAh, GP Batteries) obtained with a size of 1cm 2 A NiOOH-based cathode was used to pair with the anode. In the cells reported in this paper, the overall capacity ratio of the cathode to the anode was 3:1 to 4:1, as the performance of the zinc-based anode was the focus of this study. The anode and cathode were separated by a nonwoven cellulose membrane and a Celgard 3501 separator.

[0084] For batteries cycling at 40% DOD (depth of discharge), a solution of 6M KOH / 1M LiOH is used as the electrolyte. Before assembly, the anode is permeated with a 6M KOH / 1M LiOH solution containing 10wt% Ca(OH)₂. For batteries cycling at 60% DOD, the aqueous electrolyte is 9M KOH saturated with ZnO. The total electrolyte volume is controlled to approximately 150 μL.

[0085] The battery operates at 25mA / cm 2Constant current cycling was performed at a charge-discharge rate (C-rate) of (0.5C) with a cutoff voltage of 1.35V–1.9V. The battery was charged at a constant voltage of 1.9V until the desired capacity was reached or the current dropped to 0.01C, before the final condition of fixed capacity was met. During discharge, the battery stopped operating by reaching the fixed capacity or a lower cutoff voltage. The DOD and C-rate were calculated based on the theoretical capacity of the anode. Polarization or LSV tests were performed at a scan rate of 1mV / s. Electrochemical impedance spectroscopy (EIS) was performed over a frequency range of 200kHz to 0.5Hz using a three-electrode split test cell (EQ-3ESTC, MTICorp) with the same structure as a coin cell, using an Ag / Ag₂O wire as a quasi-reference electrode between the cathode and anode, with a perturbation of 10mV.

[0086] Figure 4 The rate performance, evaluated through polarization testing, is shown, exhibiting considerably high discharge current and power density. This is primarily due to the high and stable conductivity and ionic conductivity of nanoporous zinc, as well as its high specific surface area, which provides more sites for charge transfer. Thanks to the unique dual-continuous structure of the nanoporous zinc of this invention, the nickel-zinc battery based on nanoporous zinc achieves a discharge current and power density of 196.4 mA / cm². 2 It can provide 264mW / cm at a current density. 2 Maximum power density.

[0087] Figure 5 It showed 25mA / cm Zn 2 (Corresponding to 0.5C, based on the theoretical capacity of the anode) Stability performance of a nickel-zinc battery with a nanoporous zinc anode during charging and discharging under 40% DOD cycling in a lean electrolyte. As shown in the figure, the rechargeable areal capacity of the nanoporous zinc anode in the nickel-zinc battery can reach 20 mAh / cm² in the first 100 cycles. Zn 2 The coulombic efficiency is close to 100%, and the specific capacity is 328 mAh / g. Zn After 100 cycles, the battery capacity gradually decreases, but the rate of decrease is quite low. After 200 cycles, the battery still has a coulombic efficiency of 90%. After 300 cycles, the battery stops operating, and only 50% of the initial capacity can be delivered.

[0088] To achieve higher energy density, a DOD greater than 40% may be urgently needed. Therefore, the inventors also tested at a charge / discharge current density of 25 mA / cm². Zn 2 The cycle stability of nickel-zinc batteries cycled at 60% DOD is shown in the following results. Figure 6 .like Figure 6As shown, although the coulombic efficiency is slightly lower than that at 40% DOD, the nickel-zinc battery based on nanoporous zinc can cycle stably for about 80 cycles before significant capacity decay occurs. When the capacity drops to half of its initial capacity, the nickel-zinc battery of this invention can eventually cycle for about 160 cycles.

Claims

1. A method for preparing integrated nanoporous zinc in an electrochemical cell, the electrochemical cell comprising a working electrode, a separator, an electrolyte, a reference electrode, and a counter electrode, wherein the working electrode comprises a conductive substrate and a zinc powder compact, wherein the zinc powder compact is obtained by densifying zinc compound powder on the conductive substrate by applying a pressure of 0.5-9 tons, the electrolyte being an alkaline solution with a hydroxide concentration of 3 M to 6 M, the method comprising applying a reduction potential of -1.4 V to -1.6 V relative to Ag / AgCl to the working electrode to reduce the zinc compound, thereby forming integrated nanoporous zinc on the conductive substrate.

2. The method according to claim 1, wherein the zinc compound is zinc oxide and / or zinc carbonate.

3. The method according to any one of claims 1-2, wherein the zinc powder briquettes further include additives that promote uniform reduction reaction.

4. The method according to claim 3, wherein the additive comprises carbon black, carbon fiber, antimony oxide and / or calcium hydroxide.

5. The method according to any one of claims 1-2, wherein the reference electrode is selected from an Ag / AgCl electrode, a mercury / mercury oxide electrode, or a standard hydrogen electrode.

6. The method according to claim 5, wherein the reference electrode is an Ag / AgCl electrode.

7. The method according to any one of claims 1-2, wherein the partition is located between the working electrode and the counter electrode, and the partition is made of a rigid organic material.

8. The method according to claim 7, wherein the rigid organic material comprises polypropylene (PP), polyethylene (PE) and / or polyetherketone (PEK).

9. The method according to any one of claims 1-2, wherein the alkali is an alkali metal hydroxide.

10. The method according to claim 9, wherein the alkali metal hydroxide comprises sodium hydroxide and / or potassium hydroxide.

11. The method according to any one of claims 1-2, wherein the electrolyte further comprises other metal ions capable of participating in the reduction reaction.

12. The method of claim 7, wherein the method further comprises adjusting the porosity of the formed nanoporous zinc and the size of the zinc fibers by adjusting the distance between the separator and the working electrode.

13. The method according to any one of claims 1-2, wherein the conductive substrate is a metal substrate.

14. The method of claim 13, wherein the metal substrate is selected from metal foam, metal foil or metal mesh.

15. The method of claim 14, wherein the metal is copper, titanium, or tin.

16. The method of claim 13, wherein the metal substrate is tin-plated.

17. An integrated nanoporous zinc having bicontinuous pores and zinc fibers, wherein each of the pores and zinc fibers has a uniform size of 200 nm to 1000 nm; wherein the integrated nanoporous zinc is prepared by the method according to any one of claims 1-16; wherein the bicontinuous nature means that the zinc fibers in the integrated nanoporous zinc are interconnected, and at least 70% of the pores in the integrated nanoporous zinc are interconnected.

18. The integrated nanoporous zinc according to claim 17, wherein the integrated nanoporous zinc is prepared by a working electrode comprising a zinc oxide powder compact, and the integrated nanoporous zinc has only a primary structure consisting of pores and zinc fibers.

19. The integrated nanoporous zinc according to claim 17, wherein the integrated nanoporous zinc is prepared by a working electrode comprising a zinc carbonate powder compact, the integrated nanoporous zinc is in the form of spherical particles as a primary structure, and the spherical particles contain bicontinuous pores and zinc fibers as a secondary structure.

20. An electrode comprising an integral nanoporous zinc according to any one of claims 17-19 and a conductive substrate thereon.

21. A battery comprising an electrode as an anode as described in claim 20.

22. The battery of claim 21, wherein the battery has a lifespan of 200 cycles at a depth of discharge of 40%, or the battery has a lifespan of 100 cycles at a depth of discharge of 60%.

23. The battery according to any one of claims 21-22, wherein the battery is a secondary battery.

24. The battery according to claim 23, wherein the secondary battery is a zinc battery.

25. The battery according to claim 24, wherein the zinc battery is a nickel-zinc battery, a silver-zinc battery, or a zinc-air battery.

Citation Information

Patent Citations

  • Hyper-dendritic nanoporous zinc foam anodes, methods of producing the same, and methods for their use

    US20170025677A1

  • Three-Dimensional Zinc Sponge Electrodes for Primary and Secondary Zinc-Containing Batteries

    US20170338479A1

  • Bulk nanoporous materials for on-site and on-board generation of hydrogen and other products

    WO2019183083A1